Measuring The Pro-Poorness of Income Growth Within An Elasticity Framework - Essama-Nssah, Boniface, 1949- 1949- (The World Bank, 2006)
Poverty reduction has become a fundamental objective of development, and therefore a metric for assessing the effectiveness of various interventions. Economic growth can be a powerful instrument of income poverty reduction. This creates a need for meaningful ways of assessing the poverty impact of growth. This paper follows the elasticity approach to propose a measure of pro-poorness defined as a weighted average of the deviation of a growth pattern from the benchmark case. The measure can help assess pro-poorness both in terms of aggregate poverty measures, which are members of the additively separable class, and at percentiles. It also lends itself to a decomposition procedure, whereby the overall pattern of income growth can be unbundled, and the contributions of income components to overall pro-poorness identified. An application to data for Indonesia in the 1990s reveals that the amount of poverty reduction achieved over that period remains far below what would have been achieved under distributional neutrality. This conclusion is robust to the choice of a poverty measure among members of the additively separable class, and can be tracked back to changes in expenditure components